Is consanguinity an impediment to child development?. (3rd May 2020) - Mete, Cem; Bossavie, Laurent; Giles, John; Alderman, Harold
Abstract : Marriages between blood relatives—also known as consanguineous unions—are widespread in North Africa, Central and West Asia, and South Asia. Researchers have suggested that consanguinity has adverse effects on child development, but assessing its impact is not straightforward, as the decision to marry a relative might be endogenous to other socio-economic factors. Using a unique data set collected in rural Pakistan, this paper assesses the extent to which consanguinity is linked to children's cognitive and physical development. It exploits grandfathers' land ownership (current and past) and maternal grandparent mortality to identify the effect of endogenous consanguinity on child development. Children born into consanguineous unions have lower cognitive scores, lower height-for-age, and a higher likelihood of being severely stunted. More importantly, adverse effects are greater after accounting for the endogeneity of consanguinity, suggesting that impacts on child development are substantial, and likely to be larger than suggested in previous studies.